Faktor Penentu Kemenangan OK Arya Zulkarnain di Kecamatan Limapuluh - Nora Altika (Dinamika Politik, 2012)
This study is a study of the determinants of election victory in the district Zulkarnain OK Arya. The focus discusses what winning the deciding factor being OK Arya. The findings of this study, there are several factors that determines the winning. First, figure OK Arya in the public so popular. Second, the existence of organizational factors GEMKARA. Third, an increase in the management aspects of running the organization. The method used is a qualitative method discriptif-an event that is intended to describe in more detail.